Sosialisasi Pemanfaatan Pekarangan Rumah Tangga sebagai Lahan Penanaman Tumbuhan Hortikultura dalam Rangka Mewujudkan Program Ketahanan Pangan di Desa Selaparang, Kabupaten Lombok Timur - Qothrunnada A.S.; Aluh Hanisa N.; Hariyadi (Universitas Mataram, 2023)
Utilization of yards is one way to support the food security program launched by the Ministry of Agriculture. The Ministry of Agriculture developed the concept of intensive use of yards with the term